The frequency of late-onset Pompe disease in pediatric patients with limb-girdle muscle weakness and nonspecific hyperCKemia: A multicenter study - TÜRKDOĞAN, DİLŞAD; ÜNVER, OLCAY (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
The aim of this multicenter study was to screen for late-onset Pompe disease in high-risk children with limb-girdle muscle weakness and nonspecific hyperCKemia using the dried blood spot (DBS) test. Seventy-two children from four pediatric neurology departments in Turkey were enrolled in the study: 37 with limb-girdle muscle weakness and 35 with nonspecific hyperCKemia. Acid alpha-glucosidase (GAA) activity Was measured on DBS by tandem mass spectrometry. Six patients tested positively for Pompe disease. In three patients, one with the limb-girdle muscle weakness and two with nonspecific hyperCKemia, this was confirmed by genetic analysis. The overall frequency of late-onset Pompe disease in the study population was 4.2%. The c.1784C>T mutation found in one patient is a new mutation whereas the c.1655T>C mutation detected in the other two patients is not novel. In conclusion, Pompe disease should be suspected in patients with limb-girdle muscle weakness and nonspecific hyperCKemia. The DBS test is a safe and reliable method of diagnosis but must be confirmed by genetic analysis. In patients with a positive DBS test and negative genetic analysis, tissue assay of GAA should be considered. (C) 2016 Published by Elsevier B.V.
Keywords: Late-onset Pompe disease; Limb-girdle muscle weakness; HyperCKemia; Dried blood spots; Enzyme replacement therapy; ENZYME REPLACEMENT THERAPY; ACID MALTASE DEFICIENCY; NATURAL COURSE; FOLLOW-UP; ADULT; MANIFESTATION; ALPHA; BLOOD